A Literature Review on the Digital Transformation of State-owned Enterprises - Fang, Zhou (International Journal of Global Economics and Management, 2024)
With the rapid development of information technology and digital technology, various industries are actively promoting digital transformation, and state-owned enterprises, enjoying strong support from national policies and possessing relatively abundant resources, could have better leveraged the advantages of digital transformation. However, their digital transformation process is not always smooth. Therefore, this paper clarifies the connotation of enterprise digital transformation, highlights the significant role of digital transformation for state-owned enterprises, analyzes the problems and challenges faced by state-owned enterprises in their digital transformation, and finally puts forward strategies to accelerate the digital transformation of state-owned enterprises, with the aim of providing suggestions for the upgrading of state-owned enterprises' digital transformation.